Progenitor mast cells and tryptase in Q fever. (June 2019) - Mezouar, Soraya; Morel, Victor; Leveille, Laury; Resseguier, Noémie; Chartier, Céline; Raoult, Didier; Mege, Jean-Louis; Vitte, Joana
Highlights: Mast cell progenitor counts were decreased in the blood of Q fever patients. Serum tryptase levels were higher in Q fever patients than in healthy donors. Numbers of circulating mast cell progenitors correlated with serum tryptase levels in Q fever patients with valvular lesions. Mast cell progenitors and serum baseline tryptase level are specifically affected Q fever patients. Abstract: Q fever is an infectious disease due to Coxiella burnetii. Following a primary-infection, C. burnetii may persist in some patients, leading to endocarditis and vascular infections. Mast cells (MCs), known for their role in allergic diseases, innate immunity and cardiac function, are produced by bone marrow, circulate as progenitors in the bloodstream and reach tissues for their maturation and activation. The latter may be estimated by measuring serum tryptase levels. We wondered if MC progenitors and tryptase were affected in Q fever. We showed a decrease in MC progenitor count in Q fever patients whereas serum tryptase levels were increased. Taken together, our results show alterations of MC numbers and activity in Q fever patients, suggesting that MC are involved in Q fever pathophysiology.